2020
DOI: 10.7554/elife.56931
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 coordinates neurite remodeling to drive synapse layer emergence in the outer retina

Abstract: Structural changes in pre and postsynaptic neurons that accompany synapse formation often temporally and spatially overlap. Thus, it has been difficult to resolve which processes drive patterned connectivity. To overcome this, we use the laminated outer murine retina. We identify the serine/threonine kinase LKB1 as a key driver of synapse layer emergence. The absence of LKB1 in the retina caused a marked mislocalization and delay in synapse layer formation. In parallel, LKB1 modulated postsynaptic horizontal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…First, we show that deletion of the LKB1 target AMPK causes nuclear translocation defects similar to that observed in LKB1 mutant mice. This is notable, because we have shown that AMPK is dispensable for other early features of OPL organization ( Burger et al, 2020 ). AMPK could participate in nuclear translocation through at least two mechanisms.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…First, we show that deletion of the LKB1 target AMPK causes nuclear translocation defects similar to that observed in LKB1 mutant mice. This is notable, because we have shown that AMPK is dispensable for other early features of OPL organization ( Burger et al, 2020 ). AMPK could participate in nuclear translocation through at least two mechanisms.…”
Section: Discussionmentioning
confidence: 83%
“…We asked whether there was a cell-intrinsic requirement for LKB1 in cones by selectively deleting Lkb1 from these cells using a cone-specific Cre line ( Figure 2A ; HRGP-Cre ; [ Le et al, 2004 ], hereinafter referred to as LKB1 CONE ). Because this Cre becomes active at P8 ( Le et al,2004 ; Dilan et al, 2018 ; Razafsky et al, 2012 ), this line enables us to assess the role of LKB1 specifically during nuclear translocation and bypass roles for this molecule in other aspects of retina development ( Burger et al, 2020 ). Deletion of Lkb1 in cones alone induced nuclear translocation defects similar to that observed in whole retina deletion ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For ease-of-use and increased application in diverse biological contexts, ExM labeling methods have been simplified (Chozinski et al, 2016;Tillberg et al, 2016) and optimized protocols have been established for applications in model systems important for developmental analysis including zebrafish (Freifeld et al, 2017), C. elegans (Yu et al, 2020), and Drosophila (Jiang et al, 2018;Gao et al, 2019a; Figures 5D-F). ExM has revealed subtle defects in the developing fly (Menon et al, 2019) and mouse visual system (Burger et al, 2020) in genetic loss-of-function deletion experiments impacting synaptogenesis.…”
Section: Super-resolution Imaging Of Neural Development and Plasticitmentioning
confidence: 99%